2020
DOI: 10.21273/horttech04698-20
|View full text |Cite
|
Sign up to set email alerts
|

Eleven-year Correlation of Physical Fruit Texture Traits between Computerized Penetrometers and Sensory Assessment in an Apple Breeding Program

Abstract: Fruit texture is a major target of apple (Malus domestica) breeding programs due to its influence on consumer preference. This multitrait feature is typically rated using sensory assessment, which is subjective and prone to biases. Instrumental measurements have predominantly targeted firmness of the outer region of fruit cortex using industry standard Magness–Taylor-type penetrometers, while other metrics remain largely unused. Additionally, there have been limited reports on correlating sensory attributes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
(30 reference statements)
2
18
0
Order By: Relevance
“…In the PCA variable factor map, juiciness and crispness were highly correlated. Similarly, previous studies reported sensory juiciness to be moderately (Evans et al, 2010;Zdunek et al, 2010;Teh et al, 2020b) to highly correlated (Cliff and Bejaei, 2018) with sensory crispness. In correlating sensory juiciness with instrumental Cn, correlation coefficients ranged from low to moderate, with r values of 0.36 (Evans et al, 2010), 0.72 (Cliff and Bejaei, 2018), and 0.33 (Teh et al, 2020b).…”
Section: Juiciness Trends Of Selections Indeterminatesupporting
confidence: 66%
See 3 more Smart Citations
“…In the PCA variable factor map, juiciness and crispness were highly correlated. Similarly, previous studies reported sensory juiciness to be moderately (Evans et al, 2010;Zdunek et al, 2010;Teh et al, 2020b) to highly correlated (Cliff and Bejaei, 2018) with sensory crispness. In correlating sensory juiciness with instrumental Cn, correlation coefficients ranged from low to moderate, with r values of 0.36 (Evans et al, 2010), 0.72 (Cliff and Bejaei, 2018), and 0.33 (Teh et al, 2020b).…”
Section: Juiciness Trends Of Selections Indeterminatesupporting
confidence: 66%
“…Similarly, previous studies reported sensory juiciness to be moderately (Evans et al, 2010;Zdunek et al, 2010;Teh et al, 2020b) to highly correlated (Cliff and Bejaei, 2018) with sensory crispness. In correlating sensory juiciness with instrumental Cn, correlation coefficients ranged from low to moderate, with r values of 0.36 (Evans et al, 2010), 0.72 (Cliff and Bejaei, 2018), and 0.33 (Teh et al, 2020b). The range in coefficients could be partially explained by the diversity of germplasm used, wherein the lower correlation coefficients are expected in a more diverse set of germplasm.…”
Section: Juiciness Trends Of Selections Indeterminatesupporting
confidence: 66%
See 2 more Smart Citations
“…Simple apple flesh firmness puncture tests can be conducted using different instruments. For example, penetrometers (i.e., Effegi) could be mounted on a drill press in older versions [ 15 ] or performed by more sophisticated instruments (i.e., MTS traction machine [ 9 ] and Mohr Digi-Test-2 [ 16 , 17 ]) that allow researchers to have a continuous record of the force with penetration [ 17 ]. Care must be taken when comparing determinations taken from the different fruit-firmness instruments, because they generate a unique set of data and sample preparation may not be same.…”
Section: Introductionmentioning
confidence: 99%